Effectiveness of Plant Growth Regulators on Growth Attributes of Different Malaysian Rice Cultivars Primed with NaCl on Germination - Zahra, Syeda Maasooma; Ibrahim, Mohd Hafiz; Nulit, Rosimah; Yaapar, Muhammad Nazmin; Maqbool, Nazimah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
Plants have a hard time in its growth and development under salt stress. Salinity stress increase the activity of antioxidants and lessen the damage that salt does, phytohormones might be a good answer. Phytohormones application has emerged as a promising strategy in modern stress management as it defends plants against various abiotic stresses. The study was planned to define whether salt primed seeds treated with plant growth regulators (PGRs) can germinate normally and which level of PGRs can better assist rice germination and seedling growth. Seeds of Malaysian rice cultivars MR263 and MR284 were presoaked with 100 mM NaCl. Salt primed seeds were then treated with 0.25, 0.5, 0.75 and 1 mM Gibberellic acid (GA3), Salicylic acid (SA) and 10, 20, 30, 40 mM Thiourea (TU) in petridishes in controlled lab conditions. The experiment was designed in factorial CRD (completely randomized design) with two factors and four replicates. The interaction between rice cultivars and treatments (PGRs) significantly affected water uptake potential, germination percentage, germination index, seedling fresh and dry weight and seed vigor index. The application of 0.25 mM GA3, 0.25 mM SA and 10 mM TU reduced the inhibitory effect of NaCl priming at germination level.